Developing a Tracer Study Application Using the ADDIE Model - Basrie Basrie; Siti Qomariah (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Universities such as UINSI Samarinda face significant challenges in program evaluation because the manual collection method of tracer studies leads to data fragmentation, which hinders strategic decision-making. To solve this problem, a web-based centralized information system application was developed using the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The system is designed with different interfaces for admins and alumni to enable efficient data management and analysis. The results of the evaluation indicated that this prototype was very successful: black-box testing confirmed all functionality was running correctly, and beta testing involving five users resulted in an average feasibility score of 87%, which indicates strong user acceptance. The research successfully resulted in validated and well-accepted applications, which provided a reliable data foundation for institutional improvement.